2017
DOI: 10.1519/jpt.0000000000000092
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Sitting Time is Associated With Decreased Mobility in Older Adults

Abstract: Sitting time in older adults can be reliably measured with a reported measure (a recall strategy) over a 1-week interval. Older adults who spend more time sitting are more likely to experience mobility limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Three of the four articles included in this review reported the assessment of total sedentary time in minutes per day [3,33,34], the other reported SB in hours/day [21]. Three studies evaluated SB objectively using accelerometer devices identified by activity<100\ counts per minute (cpm) [21,32,33], while one study evaluated the association between ST and mobility limitation using only one question [34]. In contrast, the physical disability in the studies selected was measured indirectly (3 self-reports and 1 questionnaire), which was based on the information provided by individuals.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three of the four articles included in this review reported the assessment of total sedentary time in minutes per day [3,33,34], the other reported SB in hours/day [21]. Three studies evaluated SB objectively using accelerometer devices identified by activity<100\ counts per minute (cpm) [21,32,33], while one study evaluated the association between ST and mobility limitation using only one question [34]. In contrast, the physical disability in the studies selected was measured indirectly (3 self-reports and 1 questionnaire), which was based on the information provided by individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The ADL and IADL measurement scales were the most commonly used instruments. Only two studies focused on evaluating low extremity mobility [3,34].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations